Conflicting thought styles? – Responsibility and accountability in the education of Swedish police officers - Bergman, Bengt (Policing and society, 2021)
This paper discusses how Swedish police education actors navigate the act of introducing new police officers to tasks in an organisation permeated by a new public management ideology. This study’s empirical data derive from four studies on intra-professional police educators and police probationers. By interpreting and analysing these data using a theoretical framework based on styles of thought and reflexivity, a picture of how Swedish police organisations contain two somewhat contradictory thought styles emerges. The findings indicate that a reflexive awareness of this situation is crucial for educators to properly prepare new police officers for complex and important tasks. This paper contributes to current vocational training and education methods by offering new perspectives on how professional development can be enhanced in law enforcement and similar occupations.